2021
DOI: 10.1002/pmic.202000210
|View full text |Cite
|
Sign up to set email alerts
|

Proteome reprogramming of endometrial epithelial cells by human trophectodermal small extracellular vesicles reveals key insights into embryo implantation

Abstract: Embryo implantation into the receptive endometrium is critical in pregnancy establishment, initially requiring reciprocal signalling between outer layer of the blastocyst (trophectoderm cells) and endometrial epithelium; however, factors regulating this crosstalk remain poorly understood. Although endometrial extracellular vesicles (EVs) are known to signal to the embryo during implantation, the role of embryo-derived EVs remains largely unknown. Here, we provide a comprehensive proteomic characterisation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(84 citation statements)
references
References 186 publications
(337 reference statements)
2
55
0
Order By: Relevance
“…To gain insight into the proteome composition of EV cargo and whether cell growth conditions in 2D or 3D impacted protein expression, quantitative mass spectrometry was employed ( Poh et al, 2021 ; Zhu et al, 2021 ). We report for EVs derived from cells cultured in 2D format (2D EVs), 1,266 proteins and from 3D condition (3D EVs), 1,035 proteins ( n = 5, independent replicates).…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into the proteome composition of EV cargo and whether cell growth conditions in 2D or 3D impacted protein expression, quantitative mass spectrometry was employed ( Poh et al, 2021 ; Zhu et al, 2021 ). We report for EVs derived from cells cultured in 2D format (2D EVs), 1,266 proteins and from 3D condition (3D EVs), 1,035 proteins ( n = 5, independent replicates).…”
Section: Resultsmentioning
confidence: 99%
“…We next performed proteome profiling of sEVs and their parental cells using nLC-MS/MS and data-dependent acquisition ( Rai et al, 2021c ; Kompa et al, 2021 ). We found that the proteomes of parental cells versus their derived sEVs (fraction 6–8, 1.06–1.11 g/ml) were distinct ( Supplementary Figure S2 ), with sEVs compared to cells significantly enriched in sEV markers (e.g., CD9/63/81, Alix/PDCD6IP, TSG101) ( Greening et al, 2017 ; Rai et al, 2021d ; Mathieu et al, 2021 ), which includes CD63 as well as proposed universal marker of sEVs/exosomes, SDCBP ( Kugeratski et al, 2021 ) ( Figure 1D , Supplementary Table S1 ) ( Rai et al, 2021c ; Poh et al, 2021 ). Further, we show sEVs display lower abundance for non-EV (intracellular/organelle) proteins (e.g., nucleus; HNRNPC, mitochondria; CYSC, endoplasmic reticulum; CALR) ( Poh et al, 2021 ) ( Figure 1D , Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the proteomes of parental cells versus their derived sEVs (fraction 6–8, 1.06–1.11 g/ml) were distinct ( Supplementary Figure S2 ), with sEVs compared to cells significantly enriched in sEV markers (e.g., CD9/63/81, Alix/PDCD6IP, TSG101) ( Greening et al, 2017 ; Rai et al, 2021d ; Mathieu et al, 2021 ), which includes CD63 as well as proposed universal marker of sEVs/exosomes, SDCBP ( Kugeratski et al, 2021 ) ( Figure 1D , Supplementary Table S1 ) ( Rai et al, 2021c ; Poh et al, 2021 ). Further, we show sEVs display lower abundance for non-EV (intracellular/organelle) proteins (e.g., nucleus; HNRNPC, mitochondria; CYSC, endoplasmic reticulum; CALR) ( Poh et al, 2021 ) ( Figure 1D , Supplementary Table S1 ). Using these multiple sEV inclusion proteins to verify the presence of sEVs, is in direct agreement with MISEV guidelines ( Thery et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Trophectoderm also secretes soluble biomolecules into uterine fluid [28,29]. Furthermore extracellular vesicles (EV) are released into uterine fluid from both maternal and trophectodermal surfaces [30][31][32]. EV membranes protect their 'cargo' from enzymatic degradation and deliver these biomolecules, which include proteins, lipids and miRNA, to their specific target cells, thus changing their phenotype to promote implantation [33].…”
Section: Uterine Microenvironmentmentioning
confidence: 99%